Epidemiology of blindness attributable to diabetes in Scotland: change over 20 years in a defined population. Issue 11 (7th June 2013) - Hall, H. N.; Chinn, D. J.; Sinclair, A.; Styles, C. J.
Abstract Aims To establish the incidence and prevalence of blindness attributable to diabetes in a defined population in Scotland during the period 2000–2009, and to compare these figures with published data from the previous decade in the same population. Methods All blind registrations during 2000–2009 in Fife, Scotland, UK were examined and included if diabetic retinopathy/maculopathy was the main cause of blindness. The annual incidence and point prevalence on 31 December 2009 of registered blindness attributable to diabetes were calculated in both the total population and the population with diabetes. These data were compared with figures for the period 1990–1999, using a two‐tailed t‐test, and subjected to Poisson regression analysis. Results In the population with diabetes, the mean incidence of blindness attributable to diabetes was 42.7 (sd 24.2, 95% CI 25– 60) per 100 000 per year for 2000–2009, compared with 64.3 for 1990–1999 (P = 0.062). The relative risk of developing blindness per year was 0.894 (95% CI 0.811– 0.988, P = 0.028) for 2000– 2009. The point prevalence on 31 December 2009 was 167 per 100 000 in the population with diabetes, vs 210 on 31 December 1999. Conclusion Compared with the previous decade, the prevalence of blindness attributable to diabetes has decreased in the population with diabetes, with a trend towards a decrease in its incidence. This may be a consequence of an increased denominator population, resulting from better recording of diabetes and changes to the diagnostic criteria. Over the decade 2000–2009, the incidence of blindness attributable to diabetes fell by a mean of 10.6% per year in the population with diabetes.